Morphology of salivary glands and enzymatic profiles of white (Aerodramusfuciphagus) and black (Aerodramusmaximus) edible bird's nest swiftlets - Mitin, Helen (2013)
Swiftlets are birds within the swift family Apodidae (Genus: Aerodramus) where nine species of Aerodramus use their saliva to build nest but only two species produce the edible bird’s nest (EBN), the A. fuciphagus and A. maximus. In Malaysia, A. fuciphagus the producer of white EBN are ranched in special houses equipped with bird calling system to attract the bird and with suitable in house temperature, darkness and humidity. The A. maximus, the producer of the black EBN is commonly found in the Borneo (Sabah and Sarawak) natural caves. The nest is black because 50 to 60 % of the nest consists of black feathers being glued together by saliva. Since both swiftlets come from the same species, the hypotheses of this study were to show that (1) There is no significance difference in the morphology of salivary glands between A. fuciphagus and A. maximus, (2) there are different reaction and characterization of enzymes assays between the EBN of A. fuciphagus and A. maximus and (3) there is no significance difference in the enzymes assays and ultrastructure of the gland between female and male of A. fuciphagus. The objectives of this study were (1) to define the morphology of salivary glands of A. fuciphagus and A. maximus, (2) to evaluate the presence and intensity of enzymes in the EBN of A. fuciphagus and A. maximus and (3) to define the ultrastructure of salivary glands in male and female A. fuciphagus and determine their intensity of enzymes. The A. fuciphagus and A. maximus birds were caught in selected areas of Terengganu and Gomantong Caves, Sabah, respectively. A total of 16 swiftlets were used in this study of which eight (8) was A. fuchipagus and another eight (8) were A. maximus. Birds were sacrificed using 15 mg/kg phenobarbarbitone (Doletal®, Vetoquinol) intramusculary before the salivary glands were removed and processed accordingly for microscopic and enzymatic evaluations. The histochemical staining (Alcian Blue pH 1.0, Alcian Blue pH 2.5, PAS Technique, Alcian Blue- PAS, Alcian Blue-Aldehyde fuschin) and routine Haematoxylin and Eosin staining were used for microscopic evaluations. Comparative enzymatic evaluation was also done on EBN of both species by using a semi-qualititative micro method colour metric test kits. The salivary glands of male and female A. fuciphagus were also collected for scanning electron microscope (SEM), transmission electron microscope (TEM) and comparative enzymatic of the salivary glands also was done using the semi-qualititative micro method colour metric test kits. The results showed that the major gland (submandibular gland) was larger and it may vary in size. The glands stained using Alcian blue pH 1.0 and pH 2.5 showed a stronger reaction intensity of all the glangs Alcian blue pH 2.5 indicated that the glands consist of more carboxyl than sulphated mucins. In the lingual gland, the preglottal portion showed stronger reaction than the lingual portion. The glands were stained blue with Alcian Blue-PAS staining indicating the glands were acidic mucin. The Aldehyde Fuschin-Alcian Blue pH 2.5 staining showed the blue discoloration of the glands indicated that the glands were carboxylated mucin and in PAS staining. Generally all the glands were strongly stained with magenta dicoloration indicating that the presence of glycogen. The salivary glands of both A. fuciphagus and A.maximus were acidic carboxylated mucin type. Qualitative enzymatic profilling showed that eight (8) types of digestive enzymes detected the in white EBN, while in black EBN there were ten (10) digestive enzymes detected using the ApiZYM®. The Black EBN showed better positive reaction compared to the white EBN. Moderate enzymes intensity (2+ to 4+) was detected for alkaline phosphatase, acid phosphatase and ß-galactosidase. Descriptive ultrastucture evaluation of the salivary glands in both male and female swiftlets showed no morphologically difference. Both sexes of the birds also showed high enzymes intensity (4+ to 5+) compared to a standard color chart and graded on the qualitative 0 to 5+ scale (reactions with reading of >3 (20 nmols) were considered strongly positive; 1 and 2 were considered weakly positive; and 0 was considered as negative/no activity) for alkaline phosphatase, leucinearylamidase, valinearylamidase, acid phosphatase, Naphthol-AS-BI-phosphohydrolase, ß-galactosidase and ß-glucuronidase in all oral glands. These studies provides a fundamental knowledge about the anatomical differences of the salivary glands in the white (A. fuciphagus) and black (A. maximus) and the enzymatic profilling of the salivary gland and EBN which can be used or manipulated to boost the swiftlets industry.